Rapid Economic Growth but Rising Poverty Segregation: Will Vietnam Meet the SDGs for Equitable Development? - Hai-Anh H. Dang; Shatakshee Dhongde; Minh Do; Cuong Viet Nguyen; Obert Pimhidzai (Global Labor Organization (GLO), 2023)
Vietnam is widely regarded as a success story for its impressive economic growth and poverty reduction in the last few decades. Yet, recent evidence indicates that the country's economic growth has not been uniform. Compiling and analyzing new extensive province-level data from the Vietnam Household Living Standards Surveys (VHLSSs) for every alternate year between 2002 and 2020 and other data sources, we find within-province inequality to be much larger than between-province inequality. Furthermore, this inequality gap is rising over time. Despite the country's fast poverty reduction, the poor were increasingly segregated in certain provinces. We find beneficial impact of economic growth on poverty reduction, but this can depend on inequality levels. We also find greater inequality to have negative impact on economic growth and poverty reduction. Our results suggest that policy makers in Vietnam should focus on reducing spatial disparities and income inequality in order to attain sustainable economic development.
Keywords: C15; D31; I31; O10; O57; 330; poverty; inequality; pro-poor growth; convergence; household surveys; Vietnam